Enhancing psychosocial support through positive youth development: narratives from orphans in Zimbabwe - Mutambara, Julia (Omics Publishing Group, 2016)
Due to the AIDS pandemic more and more youths are losing their parents. They are usually left with caregivers and in Zimbabwe these are usually people from the extended family. Many studies have focused on orphan hood challenges in line with the deficit model. Research in the past years has challenged a dominant stereotype of youth as carriers of risk and focused instead on their strengths and potential. This qualitative exploratory study interrogates aspects of positive youth development among the orphaned youths in Zimbabwe. Data were collected from a purposive sample of 23 adolescents (15-19 years). Three focus group discussions with five participants per group were done. In depth interviews were done with 8 participants and these were not the same as those who took part in the focus group discussions. Interviews were done at the premises of two NGO that provided the adolescents with food, school fees and other material needs. Data were thematically analysed. Results suggested that the participants experienced positive development in the following areas- personal experiences, relationships with significant others and help from the community. Subthemes were also derived from the main themes above. It was recommended that psychosocial support programs mainly focusing on positive youth development be implemented to enhance the wellbeing of orphans in Zimbabwe.